1994
DOI: 10.1021/bi00197a025
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Enzymes of Thiobacillus ferrooxidans. Kinetic Properties of an Acid-Stable Iron:Rusticyanin Oxidoreductase

Abstract: Rusticyanin is an acid-stable, soluble blue copper protein found in abundance in the periplasmic space of Thiobacillus ferrooxidans, an acidophilic bacterium capable of growing autotrophically on soluble ferrous sulfate. An acid-stable iron:rusticyanin oxidoreductase activity was partially purified from cell-free extracts of T. ferrooxidans. The enzyme-catalyzed, iron-dependent reduction of the rusticyanin exhibited three kinetic properties characteristic of aerobic iron oxidation by whole cells. (i) A survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 30 publications
2
43
0
Order By: Relevance
“…6B, where the concentrations of respiratory proteins in the periplasm are orders of magnitude higher than any encountered in published in vitro functional studies. Studies conducted in dilute solutions have shown the following: (i) rusticyanin forms a complex with the periplasmic cytochrome c that lowers the standard reduction potential of the blue protein (14), and (ii) the transfer of electrons from soluble Fe(II) to rusticyanin is catalyzed by the outer membrane cytochrome c via a transient encounter-Michaelis complex (7,12). It is not a stretch of the imagination to hypothesize that additional interactions that serve to further influence their function and reactivity occur among the respiratory proteins at these high concentrations in the periplasm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6B, where the concentrations of respiratory proteins in the periplasm are orders of magnitude higher than any encountered in published in vitro functional studies. Studies conducted in dilute solutions have shown the following: (i) rusticyanin forms a complex with the periplasmic cytochrome c that lowers the standard reduction potential of the blue protein (14), and (ii) the transfer of electrons from soluble Fe(II) to rusticyanin is catalyzed by the outer membrane cytochrome c via a transient encounter-Michaelis complex (7,12). It is not a stretch of the imagination to hypothesize that additional interactions that serve to further influence their function and reactivity occur among the respiratory proteins at these high concentrations in the periplasm.…”
Section: Discussionmentioning
confidence: 99%
“…A number of laboratories have described redox-active proteins expressed by At. ferrooxidans that might participate in the iron respiratory chain (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Perhaps the most generally accepted model for the iron respiratory chain of At.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sulfate is known to bind preferentially to Fe 3+ relative to Fe 2+ , the effect is to significantly reduce E III/II couple's E° value (Table 1). The external electron transport chain between the Fe(III/II) and O 2 /H 2 O couples has been intensively studied (Rohwerder et al, 2003;Ingledew and Cobley, 1980;Shute 1987 and1994;Brasseur et al, 2004; M A N U S C R I P T ACCEPTED MANUSCRIPT Elbehti et al, 1999 and2000;Malarte et al, 2005) and redox active components have been characterised. These redox mediators appear to have either iron (Castelle et al, 2008) or copper as their redox active centre (Ida et al, 2003;McGinnis et al, 1986;Kyritsis et al, 1995;Giudici-Orticoni et al, 1999 Our interpretation of (dII/dt)/N patterns observed in Fig.…”
Section: Complexation Effectsmentioning
confidence: 99%
“…[1][2][3] Aerobic respiration on iron is the principle metabolic activity of the chemolithoautotrophic bacterium Acidithiobacillus ferrooxidans, which obtains all of its energy for CO2ˆxation and growth from oxidation of ferrous ions. [4][5][6][7][8][9][10] In that process, A. ferrooxidans uses rusticyanin as an electron transfer protein within its oxidative respiratory chain. 4,5,[10][11][12][13][14][15] This type I protein belongs to the copper protein superfamily the members of which are widely distributed in numerous organisms, 13,16) however, rusticyanin is the only member known to have both the high redox potential (+680 mV) necessary for an electron carrier and acid stability at pH 2-3 where A. ferrooxidans thrives.…”
mentioning
confidence: 99%